The Impact of a Psychological Capital Micro-Intervention on Academic Engagement within a Student-University Context - Passos, Monique (University of the Witwatersrand, Johannesburg, 2024)
Although the student experience is commonly praised for its empowerment, learning opportunities, and adventurous nature, it is important to acknowledge that students also face substantial pressure and stress throughout their academic journeys. This has been known to adversely affect student engagement (i.e., vigour, dedication, and absorption) levels, potentially diminishing academic performance and productivity levels, and increasing the likelihood of university dropouts (Jafri, 2017; Kuh et al., 2008). Fortunately, psychological capital (PsyCap); the combination of four psychological capacities (hope, self-efficacy, optimism, and resilience), has been cited as a significant contributor of academic engagement (Luthans et al., 2016; You, 2016). These constructs are explained by the Job Demands- Resources (JD-R) model as well as the Conservation of Resources (COR) theory. However, few studies have considered the relationship between PsyCap and academic engagement amongst first-year university students. This provided a unique and novel context for application, warranting future research. Thus, the purpose of the current study was to examine whether a micro PsyCap intervention had an effect upon the levels of academic engagement experienced by first-year university students. The following three instruments were combined into an online questionnaire and used to collect the necessary data for the current study: 1) A demographic questionnaire was administered to gather information about the sample and sample characteristics; 2) the Utrecht Work Engagement Scale for Students (UWES-S) was used to measure academic engagement; 3) the Psychological Capital Questionnaire (PCQ) was used to measure psychological capital and/or personal resources. Data was collected at two different time periods (i.e., pre-intervention/time 0 and post-intervention/time 1), whereby the PCQ was used to measure levels of PsyCap, and the UWES-S was used to measure academic Abstract 6 engagement. The data was analysed using descriptive statistics, correlational analysis, and mixed-model analysis of variance (ANOVA). The final sample (N = 319) consisted of both full-time and part-time first-year students across different faculties of study (i.e., Humanities, Health Sciences, and Commerce, Law, and Management) at the University of the Witwatersrand in Johannesburg, South Africa. Results of the current study demonstrated that a positive relationship exists between PsyCap and academic engagement. Specifically, the study revealed that students with higher levels of PsyCap tend to show more energy and enthusiasm (vigour), stronger commitment (dedication), and deeper absorption in their learning (absorption). These findings were supported by previous research. However, the current study also revealed that the proposed PsyCap intervention failed to significantly affect the students’ levels of vigour, dedication, and absorption over time. These results were surprising considering previous research but may be attributed to the inherent difficulties of developing an online intervention in South Africa, where there are significant variations in resource availability and economic status (especially amongst university students). Based on these challenges, future studies should incorporate face-to-face interventions to ensure inclusivity and participation from all participants; use larger and more representative samples; and embrace a mixed-methods approach to gain a deeper understanding of participant experiences. Nevertheless, the study’s result does not invalidate prior research that has demonstrated the effectiveness of PsyCap interventions in enhancing academic engagement amongst university students. Abstract 7 This study confirms a link between psychological capital (PsyCap) and student engagement, underlining the importance of personal resources in the student-university context. Further research is necessary to develop more effective iterations of the proposed PsyCap intervention aimed at effectively enhancing academic engagement and promoting overall student success
A research report Submitted in fulfillment of the requirements for a Degree of MA (Organisational Psychology) by Coursework and Research , In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Psychological capital; PsyCap; engagement; academic engagement; Job Demands- Resources model; JD-R; Conservation of Resources theory; COR; micro intervention; first- year university students; South Africa; SDG-4: Quality education